The Role of Information Technology in Improving the Efficiency and Productivity of Human Resources in the Workplace - Prety Diawati; Silvy Sondari Gadzali; Mohd Kasturi Nor Abd Aziz; Abu Muna Almaududi Ausat; Suherlan Suherlan (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
The ubiquity of information technology in contemporary society has rendered it an indispensable component across a wide range of domains. The utilization of information technology has had a noteworthy influence on enhancing efficiency and productivity in diverse domains, encompassing the professional milieu. The Human Resources function is a crucial element within an organization, playing a significant role in driving the success and expansion of the company. The objective of this investigation is to scrutinize the function of IT in enhancing HR efficacy and output within the workplace. It is crucial to comprehend the ramifications of IT employment within an organizational framework. The primary emphasis of this investigation is qualitative in nature. The process of data collection involves meticulous observation and recording of data, followed by the application of analytical methods such as data reduction, visualisation, and inference to derive meaningful insights. The research has deduced that in the constantly changing digital era, the significance of information technology in enhancing the effectiveness and output of human resources in the work environment is pivotal. IT facilitates the automation of mundane tasks, enhances collaboration, provides expedient access to information, enables effective training, supports intelligent data analysis, promotes efficient performance management, allows for work flexibility, and ensures information security.